2005
DOI: 10.3928/0147-7447-20050401-09
|View full text |Cite
|
Sign up to set email alerts
|

Cincinnati Incision Combined With Medial Rotation Fasciocutaneous Flap for Clubfeet With Pathologic Soft Tissues

Abstract: The Cincinnati approach and the medial rotation fasciocutaneous flap provides sate soft-tissue coverage, and helps avoid postoperative skin necrosis and consecutive tissue shrinking for clubfeet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…D'Souza DD et al have devised a rotation fasciocutaneous flap ( 5 ) that they found to be technically easy, scientifically logical, reproducible, and effective. Gyorgy Szabo et al found that the medial rotation fasciocutaneous flap can be effectively combined with the Cincinnati incision ( 6 ). Similarly Khan and Chinoy treated severely deformed club feet by making double zig-zag incisions (over medial foot and tendo Achilles) with no significant complications ( 7 ).…”
mentioning
confidence: 99%
“…D'Souza DD et al have devised a rotation fasciocutaneous flap ( 5 ) that they found to be technically easy, scientifically logical, reproducible, and effective. Gyorgy Szabo et al found that the medial rotation fasciocutaneous flap can be effectively combined with the Cincinnati incision ( 6 ). Similarly Khan and Chinoy treated severely deformed club feet by making double zig-zag incisions (over medial foot and tendo Achilles) with no significant complications ( 7 ).…”
mentioning
confidence: 99%